Burnout Among Anesthesiologists and Intensive Care Physicians: Results From an Italian National Survey. (July 2020) - Vargas, Maria; Spinelli, Gianmario; Buonanno, Pasquale; Iacovazzo, Carmine; Servillo, Giuseppe; De Simone, Stefania
Burnout is one of the main chronic health problems with negative consequences on caregivers but also on the quality of care. This is a multidimensional occupational syndrome, characterized by three main criteria: emotional exhaustion (EE), depersonalization (DP), and low personal accomplishment (PA). Burnout is particularly identified in professionals working in caregiving and human services, especially the ones who are interpersonally stressed and emotionally vulnerable. Intensive care professionals seem to face a critical risk of burnout. This study aiming to evaluate the occurrence and the risk factors of burnout among Italian anesthesiologists and intensive care physicians. All members included in the mailing list of the Italian Society of Anesthesia, Analgesia, and Intensive Care were invited to participate in an online survey. An anonymous questionnaire was distributed via a specific website. Burnout was measured using the Maslach Burnout Inventory (MBI) questionnaire. All responses were evaluated through univariate and multivariable logistic regression. A total of 859 physicians out of 3, 654 (23.5%) participated in this online survey. According to the MBI criteria for a high degree of burnout, 10.2% (88) of the respondents reported high EE, high DP, and low PA together; 79.9% (686) exhibited a moderate degree of burnout; and 9.9% (85) reported a low degree of burnout, with normal values in all three of the explored psychological dimensions. This study reported mostly a moderate level of burnout among Italian anesthesiologist and intensive care physicians since we found 10.2% incidence for high degree of burnout according to the MBI criteria.